The role of learning in the selection for dietary protein by sheep - Arsenos, Georgios Ioanni (The University of Edinburgh, 2001)
The purpose of this thesis was to investigate in a series of five experiments the role of learning in the selection for dietary protein by sheep.

Experiment 1 investigated whether an ‘unlearned’ appetite for dietary protein exists in sheep, and whether such an appetite depends on the previous protein feeding of the animal and the source of dietary nitrogen. No evidence was found for such an unlearned appetite; selection for protein was a learned response, which depended on the source of dietary protein of the foods offered as a choice. Subsequently, emphasis was given to the dietary factors that affect learning to select for dietary protein by sheep. This was done by the use of a classical conditioning methodology.

Experiment 2 tested the hypothesis that a continuum links the development of learned preferences and aversions towards a food flavour associated with the post-ingestive consequences (PIC) induced by the administration of a rumen degradable protein (RDP) source. The results showed that sheep are able to distinguish between two flavoured foods associated with increasing doses of a RDP; whereas small doses led to the conditioned flavour preferences (CFPs), higher doses led to conditioned flavour aversions (CFAs). It was concluded that the diet selection for protein by ruminants could be influenced quantitatively by RDP provision. A model to account for the conditioned response of an individual sheep towards administration of increasing doses of the same nutrient was put forward.

Experiments 3 and 4, tested whether a delayed type of learning could account for the development of CFPs and CFAs by sheep towards food flavours associated with PIC induced by the administration, at different points in time, of either a low or a high dose of RDP, respectively. The results showed that the temporal contiguity between the consumption of the flavoured food and the administration of the low or the high dose of RDP did not affect the development of either CFPs or CFAs. It was concluded that a process of delay learning applied to both the development of CFPs and CFAs by sheep.

The final experiment tested whether sheep are able to develop conditioned responses for food flavours when they are associated with a protein source that is undegradable in the mmen, but readily digestible (DUP) within the post-ruminal digestive tract. In particular, the relative importance of either RDP or DUP as well as their concurrent administration (RDP+DUP) in the development of conditioned responses were investigated. Sheep developed CFPs towards food flavours associated with the administration of both RDP and DUP. In addition sheep were able to distinguish between food flavours associated with the administration of either RDP or DUP; they preferred flavours associated with DUP over flavours associated with RDP. Flowever, such preferences did not develop when DUP was administered concurrently with RDP.

The results of the above experiments were characterised by a considerable variation in the feeding responses between individual sheep. To see clearly the effects of the variation between individuals on the diet selected by groups, a model of group diet selection was developed. Based on simple assumptions about the characteristics of the individuals in a population, including the variation between them, the model confirms the view that their feeding responses could be masked by averaging the data from animals which are treated the same. Possible extensions of the model to allow such variation to be accurately estimated were proposed.

The role of conditioned feeding responses in the control of food intake and diet selection of ruminants for a diet, which meets their requirements at a particular point in time, is considered in the General Discussion.